Extracorporeal Photopheresis for Treatment of Acute and Chronic Graft Versus Host Disease: An Italian Multicentric Retrospective Analysis on 94 Patients on Behalf of the Gruppo Italiano Trapianto di Midollo Osseo. Issue 12 (December 2016) - Malagola, Michele; Cancelli, Valeria; Skert, Cristina; Leali, Pierino Ferremi; Ferrari, Emilio; Tiburzi, Alessandra; Sala, Maria Luisa; Donnini, Irene; Chiusolo, Patrizia; Mussetti, Alberto; Battista, Marta; Turra, Alessandro; et al.
Abstract : Background: Extracorporeal photopheresis (ECP) is considered a valid second-line treatment for acute and chronic graft versus host disease (GVHD). Methods: Ninety-four patients with acute GVHD (aGVHD) (n = 45) and chronic GVHD (cGVHD) (n = 49), retrospectively recruited in 6 Italian centers, were submitted to ECP for second-line treatment. At the time of ECP, 22 (49%) and 23 (51%) of 45 patients with aGHVD were nonresponsive and in partial remission (PR) after steroids, respectively, and all the 49 patients with cGVHD were steroid refractory. Results: Forty-one (91%) of 45 patients with aGVHD achieved complete remission (CR) after ECP. Fifteen (33%) of 45 patients developed cGVHD. The CR rate in patients who started ECP being nonresponsive and in PR after steroid was 86% and 96%, respectively. After a median follow-up of 20 months (range, 2-72), 15 (33%) of 45 patients developed cGHVD and 16 (35%) of 45 patients died, in 3 cases for aGVHD. A trend for a better survival was seen among patients who started ECP in PR after steroid (80% vs 50% at 2 years; P = 0.07). Overall, 22 (45%) of 49 patients and 17 (35%) of 49 patients with steroid refractory cGHVD achieved CR and PR after ECP, respectively. After a median follow-up of 27 months, 44 (90%) of 49 patients are alive, 21 of whom (48%) are on steroid. Conclusions: Extracorporeal photopheresis is confirmed as an effective second-line treatment in both aGVHD and cGVHD, because it can induce a response in more than 80% of the patients and a long-term survival in at least 50% of the cases. Abstract : This retrospective analysis of 94 patients from 6 Italian centers shows that extracorporeal photopheresis can be used for treatment of nonresponsive and partially steroid responsive acute and chronic graft-versus-host disease with complete remissions in 91 percent and 45 percent, respectively.